2022
DOI: 10.1097/md.0000000000032057
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology study of mechanism and efficacy of Jiawei Huanglian-Wendan decoction in polycystic ovary syndrome with insulin resistance

Abstract: Polycystic ovary syndrome (PCOS) is a common reproductive metabolic disorder, normally accompanied by insulin resistance (IR). The specific pathogenesis of this disease remains unclear. To identify the underlying pathogenesis of PCOS with IR and explore the potential efficacy and mechanism of Jiawei Huanglian-Wendan decoction (JHWD) by a network pharmacology approach. The effective components and the potential drug and disease-related targets are retrieved. Drug-disease overlapped targets are being obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…PCOS is a heterogeneous endocrine disease featured by ovarian dysfunction, androgen excess and polycystic ovarian change. Currently, TCM possesses distinct advantages such as multiple targets and fewer side effects, which is widely applied to treat PCOS in clinical practice [ 29 ]. In this investigation, we aimed to uncover the therapeutic effects and possible mechanism of BSHLD in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is a heterogeneous endocrine disease featured by ovarian dysfunction, androgen excess and polycystic ovarian change. Currently, TCM possesses distinct advantages such as multiple targets and fewer side effects, which is widely applied to treat PCOS in clinical practice [ 29 ]. In this investigation, we aimed to uncover the therapeutic effects and possible mechanism of BSHLD in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…[Fabaceae; Glycyrrhizae Radix et Rhizoma] (Gancao, GC) ( Figure 1A ). Studies have confirmed that HWD could be mainly used to treat vascular and metabolic disorders, including atherosclerosis and type 2 diabetes, suggesting its regulation in glucose and lipid metabolism ( Li et al, 2021 ; Shi et al, 2022 ). In our clinical practice, we prescribe HWD to patients diagnosed with insomnia, which can achieve excellent therapeutic outcomes ( Li et al, 2022 ), suggesting that HWD can be used as an alternative treatment option for insomnia.…”
Section: Introductionmentioning
confidence: 99%